2022
DOI: 10.1109/access.2021.3140015
|View full text |Cite
|
Sign up to set email alerts
|

Generative Deep Learning to Detect Cyberattacks for the IoT-23 Dataset

Abstract: The rapid growth of Internet of Things (IoT) is expected to add billions of IoT devices connected to the Internet. These devices represent a vast attack surface for cyberattacks. For example, these IoT devices can be infected with botnets to enable Distributed Denial of Service (DDoS) attacks. Signaturebased intrusion detection systems are traditional countermeasures for such attacks. However, these methods rely on human experts and are time-consuming in terms of updates and may not exhaust all attack types es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 46 publications
0
19
0
1
Order By: Relevance
“…Finally, by benchmarking our approach against existing approaches for detecting zero-day attacks (see Table 1), we observed that OCSVM achieved the best MCC of 74%, precision of 84%, recall of 95%, and F 1 score of 85% using the semi-supervised approach. A comparison of our results with those obtained by [27] in approach can also be compared to DL approaches, such as those adopted in [30], which achieved an F 1 score of 85%.…”
Section: Table 19mentioning
confidence: 77%
See 1 more Smart Citation
“…Finally, by benchmarking our approach against existing approaches for detecting zero-day attacks (see Table 1), we observed that OCSVM achieved the best MCC of 74%, precision of 84%, recall of 95%, and F 1 score of 85% using the semi-supervised approach. A comparison of our results with those obtained by [27] in approach can also be compared to DL approaches, such as those adopted in [30], which achieved an F 1 score of 85%.…”
Section: Table 19mentioning
confidence: 77%
“…Abdalgawad et al [30] demonstrated that DL methods including adversarial autoencoders (AAE) and bidirectional adversarial networks (BiGAN) are effective for detecting zero-day network attacks. These methods were evaluated on the IoT-23 dataset, which comprises of 15 network attacks and 19 network traffic features.…”
Section: A Network Intrusion Detection Sytemsmentioning
confidence: 99%
“…The authors in [12] used Bidirectional Generative Adversarial Networks (BiGAN) and Adversarial Autoencoders (AAE) to detect malware in network traffic based on the full IoT-23 dataset version. The proposed models outperformed traditional ML such as RF, by getting an f1-score of 99.…”
Section: Related Workmentioning
confidence: 99%
“…However, these studies are not analyzed all existed labels of the IoT-23 dataset. For example, the authors in [8] involved detection for four malware types, while in [9] and [10] papers only five malware types were classified, and eight and nine malware types were analyzed in [11] and [12], respectively. Finally, in ML context RF and boosting algorithms are the best candidates for the proposed security system.…”
Section: E Lstm Classifier's Experimentsmentioning
confidence: 99%
“…Abdalgawad et al [9] empregaram os modelos AAE (Adversarial Autoencoders) e BiGAN (Bidirectional Generative Adversarial Networks) de aprendizagem profunda generativa para classificar os ataques do conjunto IoT-23. Foram obtidas alta acurácia de classificação de ataques conhecidos (escore F 1 na ordem de 99%) e capacidade de detectar ataques zeroday (ou seja, ameaças recém descobertas, para as quais ainda não há solução) com escore F 1 variando de 85% a 100%.…”
Section: Introductionunclassified